Implicated by scale: Anthropochemicals and the experience of ecology. Issue 2 (March 2022) - Papadopoulos, Dimitris
If our worlds are unimaginable, or, ironically, perhaps even unsustainable without anthropogenic chemicals, what does it mean to live and navigate the toxic regime, this historical moment where human-made substances are so entangled with ecologies and societies that a clean up and an 'after' to our polluted worlds is almost unthinkable? Anthropogenic chemicals are produced and used at such scale that humans need a tremendous scale of alternative chemicals to replace them. Scale, the organising principle of growth, is the source of ecological degradation and, simultaneously, is a necessary component of many remediation attempts. As life is becoming more and more chemical, chemical practice is gradually becoming conscious of its flagrant disregard of its own ecological boundaries. The attempt to restore a holistic experience of ecology shapes many current attempts to develop alternative chemical practices. When chemical practice becomes obliged by ecology to respond to the environmental crisis, the search for a different approach to scale emerges. With obligation comes the quest for reparation, both as repair and as compensation for the social and ecological damage done.